Landscape archaeology in coastal areas: technology and subsistence among prehistoric populations - Guimarães, M. B. (Scientia Plena, 2012)
Two distinct fishing technologies were identified among the sambaqui population of the Saquarema Lagoonal Complex, in the Brazilian state of Rio de Janeiro: bone point technology and worked/modified fish rays and spines. These technologies were related to the acquisition of specific fish resources; worked spines were used in the capture of Micropogonias furnieri (Desmarest) and bone points used for fishing specimens of the Ariidae family. Worked spines represent the older technology, which was predominant between 6,726 cal. years BP and 3,699 cal. years BP, while the bone point technology was dominant after 3,699 years BP. We believe this quantitative change in the consumption of aquatic resources was related to environmental factors that caused variations in the mangrove ecosystem during the late Holocene.